What determines the direction of microsaccades? (Journal of Eye Movement Research, 2010)
During visual fixation, our eyes are not entirely still. Instead, small eye movements, such as microsaccades, can be observed. We here investigate what determines the direction and frequency of these microsaccades, as this information might help to clarify what purpose they serve. The relative contribution of three possible factors was examined: (1) the orienting of covert attention, (2) the spatial distribution of possible target locations, and (3) whether monocular or binocular microsaccades are considered. The orienting of covert attention and the distribution of possible target locations had a relatively weak effect on microsaccade rates and directions. In contrast, the classification of micro-saccades as binocular (occurring in both eyes simultaneously) or monocular (observed in one eye only) strongly affected both the rate and the direction of microsaccades. The results are discussed in the context of existing findings.